1980
DOI: 10.1111/j.1755-3768.1980.tb08321.x
|View full text |Cite
|
Sign up to set email alerts
|

330 Trabeculectomies a Long Time Study (3–5½ Years)

Abstract: 281 eyes out of 330 were followed during 3 to 5 1/2 years after trabeculectomy. 32 eyes were drop-outs due to death and 17 eyes due to inability to participate in the examination program. The mean age at time of surgery was 66 years. A mean pre-operative IOP of 31 mmHg dropped to a mean post-operative level of 18 mmHg. In 57% a single trabeculectomy was considered enough to control the glaucoma. Post-operative medical treatment was considered necessary in 35%. In 87% the pre-operative progress of the field def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…In Jerndal & Lundstrom's reports (1977, 1980 the need for postoperative medical treatment was stable between one and 4 years follow-up. Watson et al (1990) found no tendency for trabeculectomy to fail once drainage was established and results in the short term were almost the same as 20 years later.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In Jerndal & Lundstrom's reports (1977, 1980 the need for postoperative medical treatment was stable between one and 4 years follow-up. Watson et al (1990) found no tendency for trabeculectomy to fail once drainage was established and results in the short term were almost the same as 20 years later.…”
Section: Discussionmentioning
confidence: 91%
“…There are, however, postoperative problems involved. The long-term IOP control rate varies from 57% to 86% (Jerndal & Lundstrom 1980;Watson & Grierson 1981;Raitta & Setda 1986), being higher if cases with additional medical treatment are included. The success rate is considerably lower in secondary and aphakic glaucoma as well as after reoperations (Skuta & Pamsh 1987).…”
mentioning
confidence: 98%
“…Previous intervention, including cataract extraction/lens aspiration, 2,23,24 glaucoma filtration surgery 25 and argon laser trabeculoplasty, 9,26 are known to be major risk factors for trabeculectomy failure. Our results concur with these findings, identifying previous cataract surgery as a strong independent risk factor for failure.…”
Section: Discussionmentioning
confidence: 99%
“…A further progression of visual field loss after surgery has been reported with widely varying frequencies. For instance, according to the results by Jerndal & Lundstrom (1980) frequencies are as low as 13%, according to Boyd (1955) as high as 83%. The time of follow-up was 3-5.5 years and 6 years, respectively.…”
mentioning
confidence: 95%